Perencanaan Poros Dan Rumah Pompa Sentrifugal Dengan Kapasitas 58 Liter/detik Head 70 M Dengan Putaran 2950 RPM Penggerak Motor Listrik - Wibisono, Bryan Arda, Ir. Sunardi Wiyono, MT (2016)
The pump is a device used to move fluids from a lower pressure to a pressure higher or lower position to a higher position. One type of pump is widely used for industrial centrifugal pumps In construction machinery, found lots rotating components and mechanisms that lead to moments around the shaft. Poros in this regard has an important role especially as a medium increase style that produces business (work). A shaft that rotates in fact not in a state that is straight, but curved rotating position. At a certain rotation axis of curvature reached the maximum price. Round that led to the arch axis reaches the maximum price is called the critical round. The planned pump shaft is a centrifugal pump which has a capacity of 58 liters / second head 70 M at 2950 rpm rotation centrifugal pump is a pump in which mechanical energy is converted into hydraulic energy speed. The longer the pipe causing friction loss increases, the head installation to be increased. Keywords: Pump, critical round head, shaf